The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/0192623308329282
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Liver Injury in Heterozygous Sod2 Knockout Mice Treated with Troglitazone or Acetaminophen

Abstract: Recently, it was reported that the intraperitoneal administration of 30 mg/kg/day troglitazone to heterozygous superoxide dismutase 2 gene knockout (Sod2þ/-) mice for twenty-eight days caused liver injury, manifested by increased serum ALT activity and hepatic necrosis. Therefore, we evaluated the reproducibility of troglitazone-induced liver injury in Sod2þ/-mice, as well as their validity as an animal model with higher sensitivity to mitochondrial toxicity by single-dose treatment with acetaminophen in Sod2þ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 18 publications
2
61
0
2
Order By: Relevance
“…Ong and coworkers 19 reported that Sod2 þ/À knockout mice developed increased serum alanine aminotransferase activity and hepatic necrosis after prolonged troglitazone administration. However, Fujimoto and coworkers 20 were unable to reproduce these results. Furthermore, although enhanced SOD2 activity and subsequently increased H 2 O 2 levels can be beneficial for preventing cell proliferation and thus may be useful in cancer treatment, 21 they can also enhance lipid peroxidation, causing mitochondrial injury.…”
Section: Discussionmentioning
confidence: 95%
“…Ong and coworkers 19 reported that Sod2 þ/À knockout mice developed increased serum alanine aminotransferase activity and hepatic necrosis after prolonged troglitazone administration. However, Fujimoto and coworkers 20 were unable to reproduce these results. Furthermore, although enhanced SOD2 activity and subsequently increased H 2 O 2 levels can be beneficial for preventing cell proliferation and thus may be useful in cancer treatment, 21 they can also enhance lipid peroxidation, causing mitochondrial injury.…”
Section: Discussionmentioning
confidence: 95%
“…MnSOD thus limits the reaction of superoxide with nitric oxide to form the reactive nitrogen species peroxynitrite. Because the hepatotoxicity of APAP occurs with increased nitration of proteins and mitochondrial dysfunction, and MnSOD heterozygote mice have been reported to be more sensitive to APAP toxicity compared with wild-type mice (Fujimoto et al, 2009), we examined hepatic MnSOD activity and possible nitration in APAPinduced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Because of safety concerns over its use, troglitazone was withdrawn from the U.S. market in 2000. On the other hand, in preclinical species, it is very difficult to reproduce the troglitazone-induced liver injury, even when using a dose of troglitazone greater than the clinical dose (Watanabe et al, 2000;Fujimoto et al, 2009). This has hindered the clarification of the exact mechanisms of troglitazoneinduced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%